2010
DOI: 10.1002/adsc.201000016
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of β‐Proline Derivatives from Allylamines via Domino Hydroformylation/Wittig Olefination and Aza‐Michael Addition

Abstract: Under appropriate reaction conditions, a domino hydroformylation/Wittig olefination can be accomplished with derivatives of allylamines and stabilized Wittig ylides. A further highly diastereoselective aza-Michael reaction yields b-proline derivatives.These are, for example, useful as building blocks for alkaloid syntheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Although highly desirable, no single catalytic protocol for the selective synthesis of β-proline has been reported to date. We anticipated that the asymmetric hydroformylation of pyrrolines, followed by subsequent transformation of the aldehyde into the free carboxylic acid (Scheme ), would provide an atom-efficient, catalytic route for the synthesis of enantioenriched β-proline, with the added potential to perform selective, stereospecific isotope labeling of of β-proline …”
Section: Resultsmentioning
confidence: 99%
“…Although highly desirable, no single catalytic protocol for the selective synthesis of β-proline has been reported to date. We anticipated that the asymmetric hydroformylation of pyrrolines, followed by subsequent transformation of the aldehyde into the free carboxylic acid (Scheme ), would provide an atom-efficient, catalytic route for the synthesis of enantioenriched β-proline, with the added potential to perform selective, stereospecific isotope labeling of of β-proline …”
Section: Resultsmentioning
confidence: 99%
“…66 In earlier work, the same group had shown that the synthesis of α,β-unsaturated esters 71 and cyclisation to afford β-proline derivatives can also be achieved via domino hydroformylation/Wittig olefination of protected amines deriving from Ir-catalysed AAS. 67 The sequence of hydroboration and subsequent Suzuki-Miyaura coupling has also been exploited for products deriving from the Ir-catalysed asymmetric allylic amination of carbonates with o-haloanilines. Unfortunately, the reactions of these nucleophiles were characterised by lower yields than those typically observed for Ir-catalysed AAS.…”
Section: Nitrogen Nucleophilesmentioning
confidence: 99%
“…Initially,w et ried diverse aza-Michaelc onditions on an acrylate derivative. [33] This unprecedented approach on ap yrazolew as unsuccessful, possibly because of the limited electrophilicity of the electron rich carbon beta to the carbonyl. We attempted to circumvent this synthetic problem by an intramolecular Heck reactiono raradical cyclisation, [34,35] however,b oth approaches failed to deliver the desired product after exploring a range of reaction conditions.…”
Section: Resultsmentioning
confidence: 99%